The Devil Is in the Details: State-Mandated Personal Finance Education and Financial Well-Being - J. Michael Collins; Carly Urban (Institute of Labor Economics (IZA), 2025)
Research documents the positive effects of state-required financial education in high school on downstream financial outcomes but pools different types of mandates. Do state policies embedding personal finance content into another course have the same effect as those that require a standalone course? This paper considers the relative effects of the two policy levers on credit scores and subjective financial well-being, using data from states implementing these policies in similar years. Our results show that states requiring a full semester of coursework improve both credit scores and subjective measures of financial well-being, while states allowing more flexibility in implementing personal finance coursework into other classes do not.
Keywords: D12; D14; D15; G53; 330; financial education; household finance; financial well-being; credit scores